Efficient Use of a Crude Drug/Herb Library Reveals Ephedra Herb As a Specific Antagonist for TH2-Specific Chemokine Receptors CCR3, CCR4, and CCR8 - Matsuo, Kazuhiko; Koizumi, Keiichi; Fujita, Mitsugu; Morikawa, Toshio; Jo, Michiko; Shibahara, Naotoshi; Saiki, Ikuo; Yoshie, Osamu; Nakayama, Takashi (Frontiers in Cell and Developmental Biology, 2016)
Chemokine receptors CCR3 and CCR4 are preferentially expressed by Th2 cells, mast cells, and/or eosinophils, all of which are involved in the pathogenesis of allergic diseases. Therefore, CCR3 and CCR4 have long been highlighted as potent therapeutic targets for allergic diseases. Japanese traditional herbal medicine Kampo consists of multiple crude drugs/herbs, which further consist of numerous chemical substances. Recent studies have demonstrated that such chemical substances appear to promising sources in the development of novel therapeutic agents. Based on these findings, we hypothesize that Kampo-related crude drugs/herbs would contain chemical substances that inhibit the cell migration mediated by CCR3 and/or CCR4. To test this hypothesis, we screened 80 crude drugs/herbs to identify candidate substances using chemotaxis assay. Among those tested, Ephedra Herb inhibited the chemotaxis mediated by both CCR3 and CCR4, Cornus Fruit inhibited that mediated by CCR3, and Rhubarb inhibited that mediated by CCR4. Furthermore, Ephedra Herb specifically inhibited the chemotaxis mediated by not only CCR3 and CCR4 but CCR8, all of which are selectively expressed by Th2 cells. This result led us to speculate that ephedrine, a major component of Ephedra Herb, would play a central role in the inhibitory effects on the chemotaxis mediated by CCR3, CCR4, and CCR8. However, ephedrine exhibited little effects on the chemotaxis. Therefore, we fractionated Ephedra Herb into four subfractions and examined the inhibitory effects of each subfraction. As the results, ethyl acetate-insoluble fraction exhibited the inhibitory effects on chemotaxis and calcium mobilization mediated by CCR3 and CCR4 most significantly. In contrast, chloroform-soluble fraction exhibited a weak inhibitory effect on the chemotaxis mediated by CCR8. Furthermore, maoto, one of the Kampo formulations containing Ephedra Herb, exhibited the inhibitory effects on the chemotaxis mediated by CCR3, CCR4, and CCR8. Taken together, our data suggest that these crude drugs/herbs might be useful sources to develop new drugs targeting Th2-mediated allergic diseases.